A Conceptualization of Militarization in Domestic Policing. (December 2019) - Simckes, Maayan; Hajat, Anjum; Revere, Debra; Rowhani-Rahbar, Ali; Willits, Dale
Researchers have investigated the underlying mechanisms and consequences of militarization in law enforcement agencies for decades, yet there is no agreed-upon definition for this concept. Without consensus, discourse and research on the intersection of policing and community well-being are hampered. The aim of this study was to develop a comprehensive framework for the concept of "militarization." Twelve key informant interviews focused on defining militarization were conducted with subject matter experts representing expertise in fields such as policing, criminal justice, and community activism. Interview transcripts underwent qualitative analysis using grounded theory methodology. Five key domains emerged: Gear/Technology, Protocols/Procedures for Community Interaction, Military Tactics, Officer Culture/Mindset, and Training and Requirements. Militarization is a complex concept whose subordinate dimensions warrant further investigation independently and in relation to the larger context. This study provides a unifying framework, contextualizing previous efforts to study militarization while highlighting areas for future study around officer and community safety.